Make In India': A Dream Come True for Young Entrepreneur - Dr. Ajay Singh (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
The Prime Minister Narendra Modi, prior to the commencement of his maiden US visit, last month launched ‘Make in India’, a major national initiative which focuses on making India a global manufacturing hub. Key thrust of the programme would be on cutting down in delays in manufacturing projects clearance, develop adequate infrastructure and make it easier for companies to do business in India. The 25 key sectors identified under the programme include automobiles, auto components, bio-technology, chemicals, defence manufacturing, electronic systems, food processing, leather, mining, oil & gas, ports, railways, ports and textile. Keywords: commencement, infrastructure, manufacturing projects, food processing.